The decline of Almohad power in al-Andalus and the loss of Majorca according to the book "Ta’rīkh Mayūrqa" by Ibn ʽAmīra Al-Makhzūmī (582-658 H/1186-1260 AD) from Alcira (Valencia, Spain) - Roser Nebot, Nicolás (Anaquel de Estudios Árabes, 2018)
The Chronicles of Majorca, Ta’rīkh Mayūrqa, a manuscript discovered in Tindouf (Algeria) in 2001, was first published in Oran (Algeria) and Beirut (Lebanon) in 2007. It was translated into Catalan in 2008 and Spanish in 2009 by the author of this study. This text provides information and a series of details that confirm the conquering of Majorca, as well as the capture of other Andalusian cities and territories. These events were due to a number of external factors, and internal tensions between Almohads and Andalusians after the Christian victory against the Almohads in the Battle of Las Navas of Tolosa (1212). The manuscript Ta’rīkh Mayūrqa provides further information and facts about the decisive role played by internal power struggles between the Almohads and the Andalusians in the conquest of Majorca in 1229 by Jaime I of Aragon, as stated by Ibn ῾Amīra al-Makhzūmī in the aforementioned work, as well as other material about the drafting of said text.